'Sport as a Celebrative and Worshipful Act': Taking Back Sport Through Theological Reflection. Issue 3 (2nd July 2016) - Hoven, Matt
Abstract : Sport chaplains naturally take on the role of practical theologians since they help others theologically reflect on their sporting lives and thus imagine how faith can be integrated for coaches and athletes. This article presents how chaplains can engage practical theology to bring theological reflection more adequately to the complexity of contemporary sport. Based on understanding practical theology as a dialectic between sport and faith, this paper begins by reflecting on two root problems in the world of sport: its commercialization and spectacle-ization. These problems diminish sport, making it into merely a form of entertainment, and thus require a faithful alternative. This response requires promoting sport as a common good in society and, for genuine integration of sport and faith, experiencing sport 'as a celebrative and worshipful act'. These two counterpoints challenge the two root issues in sport while revealing the importance of theological reflection for taking back sport.